2005
DOI: 10.1177/01486071050290s1s62
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Costs and Patient Morbidity in the Enterally Fed Intensive Care Unit Patient

Abstract: ICU patients with significant illness severity experienced a decrease in the incidence of an important nosocomial infection that is commonly associated with increased use of ICU resources and length of stay. This decrease in patient morbidity led to substantial cost savings despite the small size of our study trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Physician staffing [20,21] Noninvasive ventilation [22,23] Ventilator associated pneumonia [24-27] Patient-to-nurse ratio [16,[28][29][30][31] SDD [32] Deep venous thrombosis [33][34][35] Mattresses or pressure-relieving beds [9] TISS score by discharge [36] Pulmonary embolism [33][34][35] Daily sedation interruption policy [37] Unplanned extubation [38,39] Decubitus [9] Use of case management approach [40] Continuous lateral rotational therapy [24,41,42] Stress ulcer [43] Computerized physician order entry [44] Interclinical transport [45][46][47] Quality of life [15] Pharmacist participation during daily rounds [16] Red cell concentrate transfusion [48,49] Hospital mortality rate [32,50] Weaning following a protocol [10] Nutrition support [51][52][53][54] Berenholtz et al: Protocol for admission and discharge [11] Glucose regulation [55,…”
Section: Indicator Selectionmentioning
confidence: 99%
“…Physician staffing [20,21] Noninvasive ventilation [22,23] Ventilator associated pneumonia [24-27] Patient-to-nurse ratio [16,[28][29][30][31] SDD [32] Deep venous thrombosis [33][34][35] Mattresses or pressure-relieving beds [9] TISS score by discharge [36] Pulmonary embolism [33][34][35] Daily sedation interruption policy [37] Unplanned extubation [38,39] Decubitus [9] Use of case management approach [40] Continuous lateral rotational therapy [24,41,42] Stress ulcer [43] Computerized physician order entry [44] Interclinical transport [45][46][47] Quality of life [15] Pharmacist participation during daily rounds [16] Red cell concentrate transfusion [48,49] Hospital mortality rate [32,50] Weaning following a protocol [10] Nutrition support [51][52][53][54] Berenholtz et al: Protocol for admission and discharge [11] Glucose regulation [55,…”
Section: Indicator Selectionmentioning
confidence: 99%
“…The PUFA content of these commercially available diets is provided in Supplemental Table 1 . Over the past 25 years, these diets have been used by hospitals and tested in several clinical trials ( 10 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, blunt force trauma patients receiving IMPACT experienced a decrease in major organ failure with no differences in ventilator-free days (VENT-free days), length of stay in the ICU, or length of stay in the hospital ( 10 ). In contrast, ARDS patients given Oxepa, a similar formulation enriched in ω-3 fatty acids, experienced a significant reduction in the number of VENT-free and ICU-free days, suggesting a greater need for mechanical ventilation and time in the ICU ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that it reduces infectious morbidity, duration of mechanical ventilation, length of stay, impaired functional capacity and the overall cost of care. [2][3][4][5][6] Despite this evidence, prevalence of malnutrition in intensive care unit (ICU) patients remains high. [7,8] This suggests that nutrition support practices (NSPs) are still suboptimal in many clinical settings.…”
mentioning
confidence: 99%